SISTEM PENDUKUNG KEPUTUSAN PENENTUKAN KREDIT PEMILIKAN RUMAH MENERAPKAN MULTI-OBJECTIVE OPTIMIZATION ON THE BASIS OF RATIO ANALYSIS (MOORA) - Al-Hafiz, Nofri Wandi; Mesran, Mesran; Suginam, Suginam (STMIK Budi Darma, 2017)
The bank is one of the financial institutions that provide a program called Home Ownership Loans or abbreviated KPR. In performing its services the bank ensures that prospective borrowers are really able to repay the approved mortgages. For that purpose, several criteria are set to the debtor wishing to apply for Home Ownership Credit. The application of MOORA method is used to calculate criteria as a requirement of the mortgage application. It is expected that the application of Multi-Objective Optimization On The Basis Of Ratio Analysis (Moora) method can assist the decision makers who remain for the debtor candidate.